Flexible suspended gate organic thin-film transistors for ultra-sensitive pressure detection - Zang, Yaping (Nat Commun, 2015)
The utilization of organic devices as pressure-sensing elements in artificial intelligence and healthcare applications represents a fascinating opportunity for the next-generation electronic products. To satisfy the critical requirements of these promising applications, the low-cost construction of large-area ultra-sensitive organic pressure devices with outstanding flexibility is highly desired. Here we present flexible suspended gate organic thin-film transistors (SGOTFTs) as a model platform that enables ultra-sensitive pressure detection. More importantly, the unique device geometry of SGOTFTs allows the fine-tuning of their sensitivity by the suspended gate. An unprecedented sensitivity of 192 kPa(−1), a low limit-of-detection pressure of <0.5 Pa and a short response time of 10 ms were successfully realized, allowing the real-time detection of acoustic waves. These excellent sensing properties of SGOTFTs, together with their advantages of facile large-area fabrication and versatility in detecting various pressure signals, make SGOTFTs a powerful strategy for spatial pressure mapping in practical applications.